Att gå från goda avsikter till god praxis - Christensen, Lena; Forsyth, Rachel ; 0000-0001-7401-2870 (Pedagogisk meritering i och för förändring, 2025)
In this chapter, we describe the work involved in developing a pedagogical framework at Lund University (LU). The work was carried out as a project. In our roles as educational developer and project manager for educational activities, we accepted an assignment to create a new framework that values pedagogical expertise. We collaborated with appointment committees, pedagogical units, representatives from various administrative departments, directors of studies, student unions, heads of departments, and faculty leadership. Step by step, we built an understanding of the different stakeholders’ needs and interests. Lund University is a highly decentralized organization, where very few decisions are made at the university-wide level, and development work is naturally closely tied to needs at the operational level. What we can contribute in university-wide projects are various frameworks and models that ensure faculties have the opportunity to work with development efforts based on their local conditions and needs. It has therefore been important to conduct the project in close collaboration with the faculties and the pedagogical development units. Based on our inventory of the current situation, two key questions were formulated. In this chapter, these questions serve as a framework for our description of the process of moving from intention to practice. We present a situational analysis and offer suggestions on how recognition and reward of pedagogical expertise can be structured.